Development and evaluation of nanobody tracers for noninvasive nuclear imaging of the immune-checkpoint TIGIT - Zeven, Katty; De Groof, Timo W.M.; Ceuppens, Hannelore; Awad, Robin Maximilian; Ertveldt, Thomas; de Mey, Wout; Meeus, Fien; Raes, Geert; Breckpot, Karine; Devoogdt, Nick (Frontiers in Immunology, 2023)
T cell Ig and ITIM domain receptor (TIGIT) is a next-generation immune checkpoint predominantly expressed on activated T cells and NK cells and is associated with poor prognosis of multiple cancers. In this study, we generated a panel of human or mouse TIGITtargeting nanobodies raised in immunized llamas and evaluated them as tracers for nuclear imaging. Nine were selected for binding to recombinant and cell expressed TIGIT with low sub-nanomolar affinities and are thermostable. In addition to the nanobodies, we designed a single-chain variable fragment derived from the clinically tested monoclonal antibody Vibostolimab, targeting TIGIT and evaluated this single-chain variable fragment alongside the nanobodies. As a proof of concept, in vivo SPECT-CT imaging was performed in mice bearing TIGIT-overexpressing tumors. A six-fold higher uptake in TIGIT-overexpressing tumor was demonstrated one hour post-injection with Technetium-99m labeled nanobodies compared to an irrelevant control nanobody. Though the single-chain variable fragment exhibited superior binding to TIGIT-expressing peripheral blood mononuclear cells in vitro, its in vivo behavior yielded lower tumor-to-background ratios at one hour post-injection, indicating that nanobodies are better suited for in vivo imaging than the single-chain variable fragment. Despite the good affinity, high specificity and on-target uptake in mice in this setting, imaging of TIGIT expression on tumor-infiltrating lymphocytes within MC38 tumors remained elusive. This is likely due to the low expression levels of TIGIT in this model. Nevertheless, the excellent affinity, high specificity and rapid on-target uptake in mice bearing TIGIToverexpressing tumors showed the promising diagnostic potential of nanobodies to noninvasively image high TIGIT expression within the tumor. These findings hold promise for clinical translation to aid patient selection and improve therapy response.